Du métro à la rue, de la désobéissance civile à la ‘Primera Línea’ : l’explosion sociale au Chili en octobre 2019 - Nathalie Jammet-Arias (Amnis)
In October 2019, Chile is the scene of a social explosion that will deeply shake a country deemed stable. The purpose of this article is to study this unprecedented social mobilization since the end of the dictatorship through the relations between the power and the demonstrators thanks to the analysis of the reactions of the government, the collaborations between the different groups, symbols used in the practices of resistance to power and to the security forces of the State and of the collective constituted by the « Front line ». The movement will be studied in according to its chronology.